Meningkatkan Hasil Belajar Routing Dinamis Melalui Project Base Learning (PjBL) pada Peserta Didik Kelas XI TKJ A SMKN 5 Solok Selatan - Riko Muliadi (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
This research was conducted to improve student learning outcomes by applying the Project Base Learning (PjBL) to the dynamic routing configuration expertise competency. This research is a classroom action research which refers to Nana Sudjana model. This research was conducted in three cycles. Each cycle consists of 2 (two) meetings, in first meeting is learning using Project-Based Learning (PjBL) by compiling written syntax and the second meeting is completing a project in the form of practice in the Cisco Packet Tracer simulation program. The researcher succeeded in achieving the classical completeness indicator in cycle III. The completeness of the final score increased by 33.3% from 50% in cycle I to 62.5% in cycle II and finally to 83.3% in cycle III.